Performance improvement in construction management - Atkin, Brian; Borgbrant, Jan (Spon research., 2010)
Novel research in construction management is often distant from existing practice. This collection of reviews serves to bridge this gap under three major themes: innovation, organisation and human behaviour, and methods and tools. It outlines a series of successful collaborative projects between industry and the academic and research communities. Many of the authors have worked in technology transfer, as change agents, resolving industrially-relevant problems by using scientifically-based research. The book reveals the source of ideas, data and results to provide a useful resou.